Subjects of diplomatic communication and specifics of their activities in Ancient China - Zhang , Siyu (Journal of the Belarusian State University. Philology, 2023)
The article is devoted to the consideration of the participants of diplomatic communication in Ancient China, as well as the cultural and national specifics of the institutionalisation of this discursive practice. The author analyses the semantics and patterns of functioning of the names of diplomatic workers in various periods of the existence of Chinese diplomacy. The author considers the dominant lexemes used to designate diplomatic employees within the six main historical eras of China: the pre-Qin era, the period of the Qin and Han dynasties, the era of the Sui and Tang dynasties, the era of the five dynasties, the period of the Song, Liao, Jing and Yuan dynasties, and the period of the Ming and Qing dynasties. Particular attention is paid to the historical development of the terminological system of Chinese diplomacy and the reasons for its change, the analysis of which helps to identify evolutionary trends in relation to the functional repertoire of diplomatic discourse.